Adapting in-person diabetes group visits to a virtual setting across federally qualified health centers - Nuñez, Daisy; Marino-Nuñez, Diana; Staab, Erin M.; Dinh, Tracy; Zhu, Mengqi; Wan, Wen; Schaefer, Cynthia T.; Campbell, Amanda; Quinn, Michael T.; Baig, Arshiya A. (Frontiers in Health Services, 2022)
Diabetes group visits (GVs) have been shown to improve glycemic control, enrich patient self-care, and decrease healthcare utilization among patients with type 2 diabetes mellitus (T2DM). While telehealth has become routine, virtual GVs remain understudied, especially in federally qualified health centers (FQHCs). We conducted a five-year cluster randomized trial with a waitlist control group to test the impact of diabetes GVs on patients’ outcomes in Midwestern FQHCs. Due to COVID-19, the 6 waitlisted FQHCs adapted to virtual GVs. FQHC staff were provided training and support to implement virtual GVs. The GV intervention included 6 monthly 1-1.5-hour long education sessions and appointments with a primary care provider. We measured staff perspectives and satisfaction via GV session logs, monthly webinars, and staff surveys and interviews. Adaptations for implementation of virtual GV included: additional staff training, video conferencing platform use, decreased session length and group size, and adjusting study materials, activities, and provider appointments. Sites enrolled a total of 48 adults with T2DM for virtual GVs. Most FQHCs were urban and all FQHCs predominantly had patients on public insurance. Patients attended 2.1 ± 2.2 GVs across sites on average. Thirty-four patients (71%) attended one or more virtual GVs. The average GV lasted 79.4 minutes. Barriers to virtual GVs included patient technology issues and access, patient recruitment and enrollment, and limited staff availability. Virtual GV facilitators included providing tablets, internet access from the clinic, and technical support. Staff reported spending on average 4.9 hours/week planning and implementing GVs (SD=5.9). On average, 6 staff from each FQHC participated in GV training and 1.2 staff reported past GV experience. All staff had worked at least one year at their FQHC and most reported multiple years of experience caring for patients with T2DM. Staff-perceived virtual GV benefits included: empowered patients to manage their diabetes, provided patients with social support and frequent contact with providers, improved relationships with patients, increased team collaboration, and better patient engagement and care-coordination. Future studies and health centers can incorporate these findings to implement virtual diabetes GVs and promote accessible diabetes care.